Chinese Ancient Coin - Uang kepeng: A Strengthener of Bali and China Relationship - RAKA, Anak Agung Gede; MARDIKA, I Made; WAHYUNI, Ni Made; WARMADEWI, Anak Agung Istri Manik (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020DO - 10.14505//jemt.v11.2(42).05, 2020)
Relations between Bali and China have been established since the Han Dynasty around 100 BC. This opinion was strengthened by the discovery of nekara, a bronze kettle drum, in Pejeng, Gianyar. The relationship between Bali and China is a trade relation in which Bali was written in the notes of Chinese traders who came to Southeast Asia in the 5 th century. One of the legacies of Chinese trade in Bali is the uang kepeng (ancient Chinese coin) which was used as a means of a transaction at that time. The existence of uang kepeng in Bali is very interesting to discuss because of the transformation of its function. Previously uang kepeng functioned as a tool for trading transactions transformed into a means of transactions in religious rituals. This research used the method of observation, literature study, and in-depth interviews to reveals the existence and role of uang kepeng or pis bolong in Bali. At present, uang kepeng has also become a craft commodity that has a role in tourism in Bali.